2022
DOI: 10.34172/icnj.2022.01
|View full text |Cite
|
Sign up to set email alerts
|

Middle Cerebellar Peduncle Lesions and Their Relation to Affective and Cognitive Impairment in Multiple Sclerosis

Abstract: Background: Cerebellum has long been known to modulate not only motor coordination but also affective and cognitive functions. This study aimed to assess the impact of middle cerebellar peduncle (MCP) lesions on affective and cognitive function in patients with multiple sclerosis (MS). Methods: This was a cross-sectional study conducted on patients with relapsing-remitting MS (RRMS). All patients were subjected to 3-Tesla magnetic resonance imaging (3T MRI), brief international cognitive assessment for MS (BIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Although studies suggested that stimulating the superior peduncle increases negative feelings in patients (Nashold and Slaughter 1969), in a more recent study, repetitive transcranial magnetic stimulation of the cerebellum mood enhancement was seen (Ferrucci et al 2012), hence, the results are contradictory. Inconsistent with our nding, a previous study has shown an association between the left middle cerebellum peduncle and anxiety and depression, which indicated a positive correlation between BIS score and this cerebellum peduncle integrity (Hamdy et al 2022). Again, our results on the cerebellum add more details to previous ndings on the association between WM integrity and behavioral and motivational traits due to performing QA analysis.…”
Section: Discussionsupporting
confidence: 88%
“…Although studies suggested that stimulating the superior peduncle increases negative feelings in patients (Nashold and Slaughter 1969), in a more recent study, repetitive transcranial magnetic stimulation of the cerebellum mood enhancement was seen (Ferrucci et al 2012), hence, the results are contradictory. Inconsistent with our nding, a previous study has shown an association between the left middle cerebellum peduncle and anxiety and depression, which indicated a positive correlation between BIS score and this cerebellum peduncle integrity (Hamdy et al 2022). Again, our results on the cerebellum add more details to previous ndings on the association between WM integrity and behavioral and motivational traits due to performing QA analysis.…”
Section: Discussionsupporting
confidence: 88%
“…Sixteen published original articles present new and novel assessments, diagnostic methods, prevention, treatment and approaches of neurological disease, and valuable epidemiological features and findings to be used worldwide. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The International Clinical Neuroscience Journal is supported by Universal Scientific Education and Research Network (USERN). The goal of (ICNJ) is to continue publishing high quality and novel studies especially in areas of tissue engineering, molecular biology, personalized medicine, degenerative diseases and neuromodulation.…”
mentioning
confidence: 99%